1999
DOI: 10.1046/j.1365-294x.1999.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellites reveal clonal structure of populations of the thelytokous ant Platythyrea punctata (F. Smith) (Hymenoptera; Formicidae)

Abstract: Parthenogenesis is often thought to constitute an evolutionary dead end as compared with sexual reproduction because genetic recombination is limited or nonexistent in parthenogenetic populations. Yet there are many species to demonstrate that parthenogenesis can initially be extremely successful under certain environmental conditions. In this study we used microsatellite markers to investigate the genetic structure of four natural populations of the neotropical thelytokous parthenogenetic ant Platythyrea punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 68 publications
1
42
4
Order By: Relevance
“…Interestingly, Baudry et al (2004) reported an average reduction of heterozygosity per generation and per individual (R) of about 0.19, a value well in the range of 0.06-0.33 (mean: 0.21) found in this study. By contrast with C. cursor, Schilder et al (1999) reported that reproduction in parthenogenetic populations of the ant Platythyrea punctata is apomictic. This suggests that different modes of thelytokous parthenogenesis evolved independently in different lineages of the Formicidae.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, Baudry et al (2004) reported an average reduction of heterozygosity per generation and per individual (R) of about 0.19, a value well in the range of 0.06-0.33 (mean: 0.21) found in this study. By contrast with C. cursor, Schilder et al (1999) reported that reproduction in parthenogenetic populations of the ant Platythyrea punctata is apomictic. This suggests that different modes of thelytokous parthenogenesis evolved independently in different lineages of the Formicidae.…”
Section: Discussionmentioning
confidence: 83%
“…Cytological analysis indicated that diploidization results from automictic parthenogenesis with central fusion, that is, the fusion of two of the four meiotic products that have a central position on the spindles and that were separated at the first meiotic division, whereas the two terminal nuclei degenerate (Verma and Ruttner, 1983;Baudry et al, 2004). In ants, thelytokous parthenogenesis has been unambiguously demonstrated in six phylogenetically distant species only: Cataglyphis cursor (Cagniant, 1973), Pristomyrmex pungens (Itow et al, 1984), Cerapachys biroi (Tsuji and Yamauchi, 1995), Platythyrea punctata (Heinze and Hö lldobler, 1995;Schilder et al, 1999), Messor capitatus (Grasso et al, 2000) and Wasmannia auropunctata (Fournier et al, 2005). In the ponerine ant P. punctata, Schilder et al (1999) showed that all individuals belonging to the same population are almost genetically identical to each other, suggesting that thelytokous parthenogenesis is apomictic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetics of thelytoky has also been studied in Plathythyrea puncata (Schilder et al, 1999a, b). This Ponerine ant species shows different modes of reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Queens and gamergates ( ¼ mated workers) reproduce sexually or through arrhenotoky, whereas unmated workers can exhibit thelytokous parthenogenesis. There is a high intraspecific variation for the type of reproduction (Heinze and Hö lldobler, 1995;Schilder et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%